The 2D:4D Digit Ratio and Primary Sjögren's Syndrome: A Window Into Prenatal Hormonal Influences on Exocrine Autoimmunity - Gür, Mustafa; Akkoc, Ramazan Fazil; Oz, Burak; Karatas, Ahmet; Koca, Süleyman Serdar (Wiley, 2026)
Objectives: The pronounced female preponderance in Sj & ouml;gren's syndrome (SS) points to a potential role for sex hormones in disease development. The ratio of the second to fourth digit (2D:4D), which serves as an indirect marker of fetal androgen exposure, has shown associations with several immune-mediated conditions. The present study assessed whether 2D:4D ratios are lower in women diagnosed with SS relative to healthy individuals. Methods: In this case-control investigation, 57 female SS patients (classified per the 2016 ACR/EULAR criteria) and 44 age-matched healthy women were recruited. The lengths of the index and ring fingers were measured on both hands with digital calipers, and digit ratios were derived. Group comparisons were conducted with Welch's t-test and supplemented by Mann-Whitney U-tests. Results: Women with SS had lower 2D:4D ratios on both sides (right: 0.938 +/- 0.030 vs. 1.011 +/- 0.024, p < 0.001; left: 0.925 +/- 0.034 vs. 1.009 +/- 0.026, p < 0.001). The observed effect sizes were large (Cohen's d > 2.6). Lower ratios were driven predominantly by elongated ring fingers rather than shortened index fingers, a pattern compatible with heightened fetal androgen exposure. Conclusions: Women with primary SS exhibit lower 2D:4D digit ratios compared with healthy controls, suggesting that a shifted prenatal estrogen-to-androgen balance may prime the immune system toward the glandular autoimmunity and exocrine dysfunction that define this disease. These findings implicate the prenatal hormonal milieu as a potential contributor to the immunological processes underlying SS pathogenesis.
Keywords: 2D:4D; autoimmune disease; prenatal androgen; Sj & ouml;gren's syndrome